An overview of flipped learning studies in Malaysia - Abd Rahman, Siti Fatimah; Md Yunus, Melor; Hashim, Harwati (Arab World English Journal, 2019)
Flipped learning has become a strategic approach for educators to implement a technologicalbased learning environment. In line with the Malaysia Education Blueprint, more and more educational institutions adopt flipped learning into their establishment in a vision to achieve students’ maximum potential. With a focus on technology, flipped learning is often linked with strategic management, excellent performance as well as the positive impact on instructors and students’ skill. The implementation of flipped learning is a way to introduce different teaching and learning ideas that can develop an active classroom. The concept is to have a balance between education and advanced technology. This paper aims to review the three research elements, which are the level of participants involved in this study, the instruments, and disciplines done by 19 researchers on the flipped learning approach. Findings show that most of the studies have significant results in the implementation of the flipped learning approach. Conclusively, flipped learning is a well-rounded approach where it can be applied in any level of education regardless of the discipline. However, longitudinal studies can be performed in order to see the long-term effects of the flipped learning approach.